Oral health behaviours and shift work barriers among Hungarian EMS personnel: a cross-sectional study - Attila Mühl; József Prugberger; Edit Kovács; Orsolya Németh (BMC Oral Health, 2026)
Abstract Background Shift-working emergency medical services (EMS) personnel face structural barriers to preventive oral care, yet national workforce data remain scarce. Objective To estimate prevalence of oral symptoms, behaviours, dental attendance, and psychosocial OHRQoL impacts among Hungarian National Ambulance Service (OMSZ) staff; assess associations with occupational enablers/barriers; and evaluate acceptability of employer-supported screening. Methods Nationwide cross-sectional anonymous online survey (13 Sep 2024–17 Apr 2025; n = 1,061; 73% men, 74% 24-hour shifts). Logistic regression examined a priori outcomes (ORs, 95% CI), adjusted for age/sex/attendance; STROBE-compliant. Results Among 1,061 respondents, 74% reported 24-hour shifts as their primary duty pattern. Over half reported current or recent dental/oral problems (54.9%), and 20% had not attended a dental check-up within the previous two years. Off duty, 33% brushed twice daily, whereas during duty about two-thirds reported regular brushing. Workplace hygiene kits were reported by 40% of respondents and were more common among 24-hour shift workers. In regression analyses, kit availability was strongly associated with daily or more frequent on-duty brushing among 24-hour staff (85% vs. 21%). Daily brushing was associated with lower odds of toothache, non-use of interdental cleaning with higher odds of hiding teeth, and rare on-duty brushing with higher odds of halitosis. Psychosocial impacts were similar across roles, and 88–90% were willing to undergo workplace screening. Conclusions Shift-constrained EMS staff face substantial, preventable oral health burdens amenable to occupational solutions. Enabling on-duty hygiene and supporting routine care are key priorities. High screening readiness supports integrating teledentistry. Consistent gaps across roles underscore the need for further longitudinal and interventional studies.